The land of forgotten girls - Kelly, Erin Entrada 1977- (Greenwillow Books, an imprint of HarperCollins Publishers, 2016)
Abandoned by their father and living in poverty with their heartless stepmother in Louisiana, two sisters from the Philippines, twelve-year-old Sol and six-year-old Ming, learn the true meaning of family